Complement Mediated Apoptosis Leads to the Loss of Retinal Ganglion Cells in Animal Model of Glaucoma - Jha, Purushottam (2011)
This study investigated the role of complement in the protection of retinal ganglion cells (RGCs) in chronic ocular hypertension model of glaucoma. Intraocular pressure (IOP) was elevated in the right eye of Lewis rats by laser photocoagulation (two treatments, 7 days apart) of episcleral and limbal veins. Left eye did not receive laser treatment and served as control. Animals were injected with cobra venom factor every fifth day starting day 7 after first laser, to deplete the complement system. Animals were sacrificed at six week post-laser. Levels of C3 split products and membrane attack complex (MAC) were elevated in the retina of eyes with increased IOP and complement depletion reduced the loss of Brn3a(+) RGCs accompanied by decreased expression of GFAP and reduced MAC deposition. In complement depleted rats with increased IOP, reduced TUNEL(+) cells in ganglion cell layer, and decreased levels of active caspase-8 and active caspase-9 was observed compared to PBS treated complement sufficient rats with increased IOP. Interestingly, complement depletion also resulted in reduction of calcium influx and levels of BAD in the retinal cells of the eyes with increased IOP. Together, our results provide evidence that complement mediated apoptosis plays a pivotal role in the loss of RGCs in chronic ocular hypertension model of glaucoma.